Outline Of The U.S. Economy02405-06 - Outline Of The U.S. Economy02405-06 (Harvard Coop, 1981)
This volume was prepared for the U.S. Department of State by Christopher Conte, a former editor and reporter for the Wall Street Journal, with Albert R. Karr, a former Wall Street Journal reporter. It updates several previous editions that were issued by the U.S. Information Agency beginning in 1981.